Glyptography of the Church Santa Ana of Yauri (Espinar-Cusco): Masons’ marks and cruciform signs - Carreño-Collatupa, Raúl (2024)
This article presents the inventory and analysis of two types of glyptographic expressions present in the temple Santa Ana of Yauri, capital city of Espinar province, Cusco: Masons’ marks and cruciform signs. The function of the marks is well determined as identification and accounting signs of the ashlars delivered by different stonecutters. The presence of the crosses is more intriguing because they do not seem to have an apotropaic function, and may rather be related to devotional expressions. It is evident that the Masons’ marks are older than the crosses and would have been engraved between the 17th and 18th centuries, during the construction of the original church, on whose remains the current building was built in the second half of the 19th century. Many of these lapidary signs have been affected by the scraping perpetrated during the restoration of the ecclesiastical complex carried out a few years ago, which also destroyed colonial pictograms of the so-called Espinar rock art style. Methodologically, photographic recording, computer tracings and examination of historical documents were used.